2015
DOI: 10.1002/chem.201503644
|View full text |Cite
|
Sign up to set email alerts
|

Dual Catalytic Decarboxylative Allylations of α‐Amino Acids and Their Divergent Mechanisms

Abstract: The room temperature radical decarboxylative allylation of N-protected α-amino acids and esters has been accomplished via a combination of palladium and photoredox catalysis to provide homoallylic amines. Mechanistic investigations revealed that the stability of the α-amino radical, which is formed by decarboxylation, dictates the predominant reaction pathway between competing mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 63 publications
(48 reference statements)
7
60
0
2
Order By: Relevance
“…122 Moreover, Tunge and co-workers reported a dual photoredox Pd catalyst system for the decarboxylative allylation of α-amino and α-phenyl allyl esters (Scheme 23b). 123 Mechanistic studies indicated that, after oxidative addition and decarboxylation, recombination can occur though radical–radical coupling (upon reduction with the photocatalyst) or via a metal-mediated pathway. Interestingly, experimental observations suggested that the operative pathway is dependent on the extent of stabilization of the incipient radical.…”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…122 Moreover, Tunge and co-workers reported a dual photoredox Pd catalyst system for the decarboxylative allylation of α-amino and α-phenyl allyl esters (Scheme 23b). 123 Mechanistic studies indicated that, after oxidative addition and decarboxylation, recombination can occur though radical–radical coupling (upon reduction with the photocatalyst) or via a metal-mediated pathway. Interestingly, experimental observations suggested that the operative pathway is dependent on the extent of stabilization of the incipient radical.…”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…Access to α‐allylated dipeptides such as 115–117 via a dual‐catalyzed photochemical transformation was reported by Tunge and coworkers in 2015 (Scheme ) . C‐terminal carboxylic acids were irradiated with blue LEDs in the presence of iridium photocatalyst 54 , Pd(PPh 3 ) 4 , and allyl methyl carbonate 114 to afford designer peptides in moderate to good yields.…”
Section: Direct Decarboxylation Of Carboxylic Acidsmentioning
confidence: 99%
“…Single‐electron oxidation of the peptide carboxylate by a photoexcited iridium catalyst induces radical decarboxylation to form the alkyl radical intermediate. Allylation is feasible through two possible pathways: (A) peptide radical coordination with the palladium π‐allyl complex followed by reductive elimination; or (B) Ir‐mediated allyl radical formation and subsequent radical‐radical coupling …”
Section: Direct Decarboxylation Of Carboxylic Acidsmentioning
confidence: 99%
“…In addition, Breit and coworkers recently disclosed photoredox/Rh catalysis for the allylation of amines, [13] demonstrating the prospects of group 9m etal catalysis in the context of metallaphotoredox chemistry. [14,15] In contrast, investigations into the corresponding catalysis with Co,the most abundant congener of group 9, have remained underdeveloped for decades.C ontrary to the potential advantages of Co catalysis,which include lower cost and inherent similarity to the versatile Rh and Ir catalysts, literature surveys on Co-catalyzed allylic alkylation with stabilized carbon nucleophiles revealed only afew examples, with inferior outcomes,c ompared to either Rh or Ir catalysis. [16] Allylic alkylations with sodium malonate catalyzed by well-defined Co I complexes were reported by Roustan in 1979, [16a] albeit with electrophiles limited to allyl chlorides and with low observed regioselectivity (Scheme 1b).…”
mentioning
confidence: 99%